Web services & SOA : principles and technology - Papazoglou, Michael P. , 1953- (Pearson Education, 2012)
"This will be an informative guide for practice nurses, specialist community public health nurses, post registration nurses undertaking a programme of study leading to recording on the professional register, pre registration student nurses undertaking a programme of study leading to entry on to the professional register, nurses working in NHS Direct, nurses working in NHS walk in centres and nurses working in the prison setting."-- BOOK JACKET